Four new species of Careproctus (Cottoidei: Liparidae) from the deep-water vicinity of the southern Kuril Islands (Western North Pacific) - Chernova, Natalia; Thiel, Ralf; Eidus, Irina (Zootaxa, 2020)
Four new species of Careproctus (Cottoidei: Liparidae) are described from the Bussol Strait (the deepest channel of the Kuril archipelago) and two neighboring abyssal basins of the Western North Pacific. Careproctus laperousei sp. nov. from the northern slope of the Kuril-Kamchatka Trench (depths of 4796–4803 m) has the following characters: vertebrae 57, pectoral-fin rays 26, principal caudal-fin rays 8 and pore pattern 2-6-7-1; it differs from the most similar congeners from the North Pacific in having a black peritoneum, short head (22.5 % of standard length, SL) and large disk (37.0 % of head length, lc). Careproctus brevipectoralis sp. nov. from the Kuril Basin of the Sea of Okhotsk (depths of 3301 m) has the following characters: vertebrae 55, pectoral-fin rays 26, caudal-fin rays 9, pore pattern 2-6-7-1 and peritoneum black; it differs from congeners by the absence of pleural ribs, deep and compressed leaf-like body (greatest depth 119 % lc, depth above anal-fin origin 113 % lc), small head (18 % SL), short pectoral fin (11 % SL) and cartilaginous-like tissue surrounding the dorsal fin. Careproctus pulcher sp. nov. and Careproctus globulus sp. nov., both having 46 vertebrae, are found on the Pacific side of the Bussol Strait at depths of 2350–2358 m. Careproctus pulcher sp. nov. is characterized by pectoral-fin rays 31–32, caudal-fin rays 10, pore pattern 2-6-7-1 and peritoneum pale; it differs from the most similar congeners in having a shorter head (25.5–26.3 % SL in adults) and gill opening reaching ventrally to 4th pectoral ray. Careproctus globulus sp. nov. has the following characters: pectoral-fin rays about 24, caudal-fin rays 8 and peritoneum black; it differs from other species in having a globular body, deep curve of vertebral column and pore pattern 2-5-6-1. Thus, based on these collections, the underwater sill of the Bussol Strait is inhabited by different species of Careproctus than the neighboring abyssal plains, Kuril-Kamchatka Trench and the Kuril Basin of the Sea of Okhotsk. Careproctus laperousei sp. nov. is the most deep-water Careproctus in the North Pacific.